Analisis Pengaruh dan Implementasi Aliran Hukum Alam (Rasional) Terhadap Sistem Hukum Indonesia dan Hukum Lingkungan di Indonesia - Ilham Daffi Syabana; Idris Idris (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
The role of theory in legal science is crucial for the understanding and integration of concepts. The history of Indonesian law shows the application of customary and Islamic law before Dutch colonization. Natural laws, especially rational flows, play a universal role in the management of water resources to maintain ecological balance. The distribution of clean water in Indonesia is influenced by land use change, mining, and industry, creating an imbalance. The identification of research problems involves the influence of Natural Law on the Indonesian Legal System and its impact on Environmental Law. The theoretical analysis highlights the contribution of Natural Law in the context of Indonesian prismatic law. Natural Law supports environmental law, especially water resources management, with an integrated approach based on natural values, relevant to achieving sustainability and ecological balance in the future.